Frequency of Use Mukena Relations With Number of Figures Germs In Mukena - Agus Subagiyo; Arif Widiyanto; Tri Cahyono (Jurnal Riset Kesehatan, 2012)
The type of research is quasi-experimental with 3 times replication. The samples of the study are 15 pieces of mukena using purposive sampling technique. Analysis of data from the measurement results, observations, and laboratory tests. The result of the study showed that the sanitary condition of the mosque with a score of 885 indicates as a good criteria, sanitary conditions inside the mosque with a score of 77.78% indicates as a good criteria, sanitary condition of Mukena storage area with a score of 42.85% indicates as poor criteria. The average temperature and the humidity of prayer room are 27.° C and 80.20%. Total number of germs on mukena is 788.4 colonies / cm ² on average, with a range between 44 colonies / cm ² up to 2561 colonies / cm ². The difference in number of germs on mukena showed that the highest number is from the frequency of usage 20 times to 40 times, which is 795 colonies / cm ². That is, the more often the mukena used, the higher the number of germs on mukena. So the number of germs on mukena is influenced by the frequency of usage.